Das Motiv der Liebesnahrung bei Apuleius, Gottfried, Petrarca und da Ponte - Adorjáni, Zsolt (Verbum – Analecta Neolatina, 2015)
In this paper I investigate an erotic motif in Gottfried's Tristan, the lovers' nourisment by their mutual love. This motif of love-begotten mysterious satiety appears in a sonnet of Petrarca and in Lorenzo da Ponte's libretto for Mozart's opera Così fan tutte. The analysis shows that a case can be made for these texts being directly influenced by the Wunschleben-scene in the work of the medieval German poet. Yet another text seems to have some bearing on this question: a passage in Apuleius's Metamorphoses (The Golden Ass) could be considered the archetype for all appearances of this strange erotic motif in different disguises. Despite the highly hypothetical character of the arguments put forth, there is some likeliness that we are dealing with a continuous tradition being alive throughout remote ages and genres.